The vocational development of a fifth form work exploration class : a thesis presented in partial fulfilment of the requirements for the Degree of Master of Arts in Applied Psychology at Massey University - Newbold, Anne Marie (Massey University, 1975)
The development of vocational maturity in a fifth form Work Exploration class was compared to that of a similar group of students who did not belong to the Work Exploration class. Vocational maturity was measured by the Crites Vocational Attitude Test, by subjective assessment in an informal interview situation, and by the Vocational Development Questionnaire which was developed specially for this study. After two school terms the results of the Crites Vocational Attitude Test and the interview showed that the experimental group (the Work Exploration Class) had developed significantly more in vocational maturity than had the control group. The Vocational Development Questionnaire did not show the same trend, therefore in its present state it is not a valid measure of vocational maturity.
Keywords: New Zealand; Vocational education; Vocational interests